Computer Science &Amp; Information Technology ( CS &Amp; IT ) 2016
DOI: 10.5121/csit.2016.60210
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Four Multi-Label Classification Algorithms in Classifying Learning Objects

Abstract: The classification of learning objects (LOs) enables users to search for, access, and reuse them as needed. It makes e-learning as effective and efficient as possible. In this article the multilabel learning approach is represented for classifying and ranking multi-labelled LOs, whereas each LO might be associated with multiple labels as opposed to a single-label approach. A comprehensive overview of the common fundamental multi-label classification algorithms and metrics will be discussed. In this article, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The procedure follows a simple way to cluster a given data set through a center number of groups (assume k clusters) fixed apriori. Classification model: Support vector machine . With the increasing number of enrollments, the demand to identify, analyze, and classify the activities in MOOCs has arisen and become a critical issue . Some classical classification models in educational domains include support vector machine, neural networks, decision trees, logistic regression, and random forest.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure follows a simple way to cluster a given data set through a center number of groups (assume k clusters) fixed apriori. Classification model: Support vector machine . With the increasing number of enrollments, the demand to identify, analyze, and classify the activities in MOOCs has arisen and become a critical issue . Some classical classification models in educational domains include support vector machine, neural networks, decision trees, logistic regression, and random forest.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental results indicated that LP with support vector machine as the base classifier achieved better classification accuracy than the counterparts. In 2016, Aldrees and Chikh investigated the multi-label classification performance of Binary Relevance One-vs.-one, Label Powerset, and Multilabel K Nearest Neighbors (MLKNN) on music and emotion datasets [9]. MLKNN performed poorly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…But, concerning the multi-class classification, the similar set of labels are combined as a distinct class. Thus, every similar set of labels that found in the training dataset is considered a new class of a multi-class classification task [15]. The most common PT methods which are based on transformation to binary classification are described in the following.…”
Section: ) Strategies Based On Pt Techniquementioning
confidence: 99%
“…The classification of a new (unseen) multilabel problem using BR is performed by transforming it into n single-label problems (where n refers to number of labels). Consequently, the new instance will be labelled with a union of the positive labels predicted by the n-binary classifiers [15], as shown in Fig. 3.…”
Section: ) Strategies Based On Pt Techniquementioning
confidence: 99%
See 1 more Smart Citation